Model Penangkaran Benih Jagung Berbasis Komunitas - Ramlah Arief; Zubachtirodin Zubachtirodin (Puslitbang Tanaman Pangan, 2012)
The model of maize seed production based on community in farmers’ fields was aimed to meet the demand of high quality of maize seed at the right time. As in many African countries, maize seed production by farmers was the solution for the timely seed demand. A model of seed production to supply maize seed by community had been carried out in some provinces of Indonesia, i.e. NTT, NTB, South Sulawesi, Central Sulawesi, and South Kalimantan. Most of the maize seed production model were collaboration between group of farmers and local seed company. Maize seed produced by farmers were depending on the seed company demand. The sustainability of the community based maize seed productions is depending on the availability of source seeds, market demand and processing facilities. Collaboration between farmers’ seed growers with private and public sectors is the key for the success of community based seed production.